Infestation of Field Dodder (Cuscuta campestris Yunck.) Promotes Changes in Host Dry Weight and Essential Oil Production in Two Aromatic Plants, Peppermint and Chamomile - Marija Sarić-Krsmanović; Ana Dragumilo; Jelena Gajić Umiljendić; Ljiljana Radivojević; Ljiljana Šantrić; Rada Đurović-Pejčev (Plants, 2020)
Peppermint (Mentha piperita L.) and chamomile (Chamomilla recutita (L.) Rausch.) are aromatic plants with considerable economic value. These plants and their essential oils are used in medicine, cosmetics, and the food industry. One of the main limiting factors in peppermint and chamomile commercial cultivation is weed competition since weeds are able to decrease both oil amount and biomass yield. The purpose of the present study was to determine the effect of parasitism by field dodder (Cuscuta campestris Yunck.) on peppermint and chamomile dry weight and their essential oil yield and composition. Essential oils from both noninfested and infested peppermint and chamomile plants were obtained by hydrodistillation and characterized chemically by gas chromatography (GC) coupled with mass spectrometry (MS). The amount of dry matter accumulated by peppermint and chamomile plants infested by field dodder was lower (25% and 63%, respectively) compared to noninfested plants. Essential oil yield increased for peppermint (3.87% (v/w) and 3.63% (v/w)), but decreased for chamomile (0.2% (v/w) and 0.5% (v/w)) both from infested and noninfested plants, respectively. The oil composition profile significantly differed in terms of content. In peppermint plants, field dodder infestation increased menthone content by 23%, and decreased the content of both menthol by 11% and pulegone by 67%. Furthermore, δ-cadinene was detected only in oil extracted from infested peppermint plants. Compared to peppermint, chamomile plants were significantly more affected by field dodder in terms of essential oil yield, as well as oil composition and plant dry weight. In chamomile plants, (E)-dendrolasin was detected in the oil of noninfested plants, and 1,4-dimethyl-7-(1-methylethyl)-azulen-2-ol was detected only in the oil of infested plants.